AWARENESS AMONG SHG MEMBERS IN BENGALURU CITY WITH REGARDS TO DIGITAL FINANCIAL SERVICES - MANJUNATHA C , DR.S. KARTHIKEYAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Financial inclusion through digital mode is playing a pivotal role in the technologically improved era. Than the conventional method, it reaches more and has become convenient for people. It significantly helps women’s economic empowerment via Self Help Groups (SHG). But the members of SHGs can enjoy entire benefits of financial inclusion through digital model, only with adequate awareness about various aspects. Hence, the researcher studied the awareness level of the members of SHGs regarding various aspects of financial inclusion through digital mode in Bengaluru city. The researcher selected both rural and urban districts of Bengaluru. From which, the researcher selected 525 SHG members proportionally on the basis of number of SHGs in each block of these two districts. The researcher collected primary data from the respondents using a well structured interview schedule. The researcher used Likert’s five-point scalling technique for collecting data. Statistical tools of mean, SD, CV, Cronbach’s Alpha test , Factor Analysis, Mann Whitney U Test and Kruskal Wallis Test are applied. The study found that SHG members in Bengaluru demonstrate reasonable familiarity with basic digital financial services such as UPI, mobile banking, and digital payments, their understanding of advanced services including digital financial instruments, online government schemes, investment platforms, and cyber-safety measures remains limited. Awareness levels vary significantly across demographic and SHG-related groups, reflecting differences in education, digital exposure, and socio-economic conditions. It is concluded that although digital financial adoption is growing, the results highlight a strong need for targeted digital literacy initiatives to bridge awareness gaps, strengthen confidence, and ensure that SHG women can fully leverage digital finance for their economic advancement.